2011
DOI: 10.1016/j.vetmic.2011.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Novel gastric helicobacters and oral campylobacters are present in captive and wild cetaceans

Abstract: The mammalian gastric and oral mucosa may be colonized by mixed Helicobacter and Campylobacter species, respectively, in individual animals. To better characterize the presence and distribution of Helicobacter and Campylobacter among marine mammals, we used PCR and 16S rDNA sequence analysis to examine gastric and oral samples from ten dolphins (Tursiops gephyreus), one killer whale (Orcinus orca), one false killer whale (Pseudorca crassidens), and three wild La Plata river dolphins (Pontoporia blainvillei). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…n. cetorum, of cetaceans (whales, dolphins)) was first isolated from the stomachs and feces of adult captive cetaceans (whales, dolphins) (Harper et al 2000(Harper et al , 2002aValidation List 2006b). And has since been detected in South American fur seals and dolphins (Goldman et al 2009(Goldman et al , 2011, Atlantic spotted dolphins (Suarez et al 2010). Interestingly, a Helicobacter species that was shown to be closely related to H. cetorum was detected in analyses of lymph node metatranscriptomes of healthy mule deer (Odocoileus hemionus) (Wittekindt et al 2010).…”
Section: Helicobacter Cetorummentioning
confidence: 99%
“…n. cetorum, of cetaceans (whales, dolphins)) was first isolated from the stomachs and feces of adult captive cetaceans (whales, dolphins) (Harper et al 2000(Harper et al , 2002aValidation List 2006b). And has since been detected in South American fur seals and dolphins (Goldman et al 2009(Goldman et al , 2011, Atlantic spotted dolphins (Suarez et al 2010). Interestingly, a Helicobacter species that was shown to be closely related to H. cetorum was detected in analyses of lymph node metatranscriptomes of healthy mule deer (Odocoileus hemionus) (Wittekindt et al 2010).…”
Section: Helicobacter Cetorummentioning
confidence: 99%
“…Pathogens that affect gastrointestinal dolphin health have been previously reviewed elsewhere (Baskin 2006;Venn-Watson et al 2008) and include astroviruses (Rivera et al 2009), Campylobacter spp. (Foster et al 2004;Stoddard 2005;Goldman et al 2011), Clostridium spp. (Buck et al 1987), Edw.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Helicobacter infections may affect the health status of dolphins by contributing to the pathogenesis of gastric ulcers. In effect, novel helicobacters have been found in wild and captive marine mammals (Goldman et al 2011). Helicobacter cetorum has been isolated from the gastric mucosa of dolphins (Harper et al 2000(Harper et al , 2002, although its relation to gastric disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter spp. has been diagnosed both in the oral cavity and digestive tract of captive and wild cetaceans (Suárez et al 2010, Goldman et al 2011). Suárez et al (2010) reported positive stomach biopsies for Helicobacter in a dolphin that also presented macroscopic ulcerations and inflammatory alterations, conditions normally present in cases of gastrointestinal disease.…”
Section: Species Number Of Individuals and Number Of Teeth Analyzedmentioning
confidence: 99%